2005
DOI: 10.1029/2004jb003097
|View full text |Cite
|
Sign up to set email alerts
|

Fractal properties of seismicity in regions affected by large, shallow earthquakes in western Japan: Implications for fault formation processes based on a binary fractal fracture network model

Abstract: [1] The temporal variation in the b value (which is defined as the slope of the Gutenberg-Richter frequency N-magnitude M relationship), log N = a À bM, and the multifractal dimension of the spatial distribution D q of seismic activity are analyzed using earthquake catalog data for regions affected by two recent large earthquakes in Japan. An anomalous decrease in D q and an increase in b value appear as a common seismic rupture response during the period of decreasing seismic energy release in the lead up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…As for the patterns of nonlinear behavior of seis micity, as we well know, there have been several differ ent patterns of nonlinear behavior of seismicity, for example, the decrease of the fractal dimensions of seismicity before great ruptures (Goltz, 1997), the steepening of curves in the generalized dimension spectrum of seismicity before great earthquakes (Nakaya, 2005;Hirabayashi, Ito, and Yoshii, 1992), and so on (Matcharashvili, Chelidze, and Javakhish vili, 2000). However, the characteristic variation of local scaling property of seismicity is not well known.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As for the patterns of nonlinear behavior of seis micity, as we well know, there have been several differ ent patterns of nonlinear behavior of seismicity, for example, the decrease of the fractal dimensions of seismicity before great ruptures (Goltz, 1997), the steepening of curves in the generalized dimension spectrum of seismicity before great earthquakes (Nakaya, 2005;Hirabayashi, Ito, and Yoshii, 1992), and so on (Matcharashvili, Chelidze, and Javakhish vili, 2000). However, the characteristic variation of local scaling property of seismicity is not well known.…”
Section: Discussionmentioning
confidence: 97%
“…The curve pre sents that D q for positive q decreases as q is increased and for negative q increases as q is decreased, which illustrates the multifractal property. Some researches show that the D q -q curves become steeper before a great rupture than during normal periods (Hiraba yashi et al, 1992;Zhu and Chen, 2000;Nakaya, 2005), i.e., D q increases for negative q and decreases for positive q. This change mainly occurs within the range of -5 ≤ q ≤ 5.…”
Section: Local Scaling Propertymentioning
confidence: 94%
See 1 more Smart Citation
“…The curve presents that D q for positive q decreases as q is increased and for negative q increases as q is decreased, which illustrates the multifractal property. Some researches show that the D q − q curves become steeper before a great rupture than during normal periods (Hirabayashi et al, 1992;Nakaya, 2005;Zhu and Chen, 2000), i.e., D q increases for negative q and decreases for positive q. This change mainly occurs within the range of −5 ≤ q ≤5.…”
Section: Local Scaling Propertymentioning
confidence: 99%
“…It has been shown in rock burst (Lu et al, 2005), petrophysical experiments (Lei et al, 2003;Lei and Satoh, 2007) and natural earthquake research (Murase, 2004;Roy and Nath, 2007) that the mono-fractal dimension displays characteristic changes before a major rupture; it Correspondence to: Q. Li (lqdzjybzx@126.com) has also been shown in multifractal research on seismic activity that the spectrum of generalised dimensions and the singularity spectrum display characteristic changes before large earthquakes (Caruso et al, 2006;Dimitriu et al, 2000;Nakaya, 2005;Roy and Padhi, 2007). Some results have confirmed that the decrease in fractal dimension, the steepening of curves in the generalised dimension spectrum and the broadening of the value range in the singularity spectrum, can be taken as indicators of an unstable state of an earthquake system before a large rupture (Carpinteri et al, 2009;Goltz, 1997;Kiyashchenko et al, 2004;Lee et al, 2008;Matcharashvili et al, 2000;Radulian and Trifu, 1991;Telesca et al, 2005;Telesca and Lapenna, 2006).…”
Section: Introductionmentioning
confidence: 99%